ForYou Projects / Hasbi Megat Zafirus ... [et al.] - Megat Zafirus, Hasbi; Rosli, Muhammad Hakimi; Rahim, Nur Athirah; Azhar, Nur Nabilah; Nor Hisham, Siti Hajar; Mohd Ghani, Siti Zulaikha (2021)
On this subject we are required to select a company for our case study. This case study is a group assignment that consist of 6 members for each group. Our group members are Hasbi, Nur Athirah, Siti Hajar, Siti Zulaikha, Nur Nabilah and Hakimi. The company that we choose is from businesswomen name Nur Zalikha Aliya binti Azhar who run a small company which selling Mini Painting by Numbers Kit. Moreover, the company name was ForYou Projects that commencing her business on 25 July 2020. Even though, still at young age she braves enough for doing this business online despite the pandemic situation of COVID-19 in the country. Nevertheless, this report provides information and analysis regarding the company for this particular assignment. The first section of this report is mainly introduction of the business that divided into background and the purpose for this study. Other than that, the second part will provide the ForYou Projects detailed information that comprises of background, organization structure, product/ services, business strategy and financial achievement. This information is vital for this report in order to investigate for company analysis. Furthermore, the next part of this report will contain our SWOT analysis based on the information of the company. The SWOT analysis are will cover on the strengths, weakness, threat and the opportunities for the company. The purpose of this analysis method was to think critically the potentials and disadvantages when a person running such business and for our SWOT, we simply put all the point in table view for better comprehension. After that, the last part for this report will have the finding and discussion for the business. For this part we will illustrate the business issues and implement the solution for the problems. From our perspective, every business will face difficulty especially in the current circumstances of lockdown and pandemic had made it more worsen. Hence, ForYou Project also having a myriad of problems. The major problem was copyright issue from other competitor and our focus will focus on the copyright issue for the company. Last but not least, will include the discussion and implementation for the main problem. Our report also will be evaluated for the solution to ensure detailed view of advantage and disadvantages of this business.